Andrological examination of Hungarian Large White and Landrace boars - Balogh, Eszter; Kern, László; Anton, István; Balogh, Orsolya; Gábor, György; Rátky, József (Acta Agraria Debreceniensis, 2018)
The Hungarian Large White and Hungarian Landrace pig breeds have outstanding lifetime performance, production parameters and crossbreeding ability. Nevertheless, during the recent decades, these breeds could not compete with the West European hybrid pigs concerning on production results. In this study, we made a complex andrological evaluation of boars in different Hungarian nucleus breeding stocks. After taking blood and semen samples, performing gonadotropin-releasing hormone (GnRH) challenge, ultrasonic and thermographic examinations were done. Laboratory tests were accomplished in reproduction labs of NARIC ABNMS. Our goal was to determine the reproductive performances of boars and collect samples for future genetic examinations, respectively.